Studying the relationship between leadership style of coaches and sportsmanship commitment of athletes (A case study of professional athletes in I.R. I. Karate Super League) - Shahram Shafiee; Mohammad Hossein Fikoouei; Noshin Benar (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: Today, when a group of people trying to reach the goal, manager and leader usually undertake the responsibility of the group. Coach renders influence on team members, while athletes work hard to achieve team goals. The purpose of the present study is relationship between leadership styles of coaches and sports actions of karate athletes. Material: The present study involves all active athletes of Super League karate in 91-92 season (N=100). The statistical sample was equal to statistical population (N=n). In order to collect information we used leadership style questionnaire Bos and Avlio (MLQ) and questionnaire of Scanlan (SCMS). Internal validity questionnaire was approved by university professors and its reliability - by Cronbach's alpha test 0.86, and 0.79. Also for data analysis we used descriptive indicators of mean and standard deviation. Preliminary analysis of data proved normaldistribution by Kolmogorov-Smirnov test. And then, we used measurements by Pearson, Spearman, Mann-Whitney U, Wilcoxon T, Friedman correlation coefficient of significance level (P-0.05). Results: there are significant differences between athletes' results and styles of leadership. There is significant correlation between the results with style Attraction (0.000), Idealized Influence (0.000), Inspirational (0.001), Intellectual stimulation (0.007), Individualized consideration (0.017), Exception Active (0.008) and Laissez-faire (0.041) (P- 0.05). Conclusions: for increased of athletes' results coach should use style Attraction, Idealized Influence , Inspirational , Intellectual stimulation , Individualized consideration, Exception Active and if coach wants to see success of his athletes at athletic fields he should comply the applied styles with sportsmen's results.